2013
DOI: 10.1002/jcp.24300
|View full text |Cite
|
Sign up to set email alerts
|

EMT markers in lung adenocarcinoma pleural effusion spheroid cells

Abstract: Epithelial-to-mesenchymal transition (EMT) is a process in which cells undergo a developmental switch from epithelial to mesenchymal phenotype. This process has been related to embryologic morphogenesis but also to cancer progression and metastasis. The aim of the current study was to investigate the expression of EMT-related markers in adherent and spheroid cell cultures derived from malignant pleural effusions (MPEs) of patients affected by lung adenocarcinoma. On the basis of efficient in vitro propagation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…EMT is a conserved cellular process in which epithelial tumor cell lacks its polarity and transforms into a mesenchymal phenotype [16, 17]. The feature of EMT occurrence is that the epithelial marker E-cadherin is downregulated and mesenchymal marker, like N-cadherin, is upregulated [18, 19]. To demonstrate whether the lncRNA-LET affected EMT, we detected the molecular marker levels of EMT and showed the inhibition of lncRNA-LET on EMT.…”
Section: Discussionmentioning
confidence: 99%
“…EMT is a conserved cellular process in which epithelial tumor cell lacks its polarity and transforms into a mesenchymal phenotype [16, 17]. The feature of EMT occurrence is that the epithelial marker E-cadherin is downregulated and mesenchymal marker, like N-cadherin, is upregulated [18, 19]. To demonstrate whether the lncRNA-LET affected EMT, we detected the molecular marker levels of EMT and showed the inhibition of lncRNA-LET on EMT.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, earlier studies have also reported the role of Slug protein in EMT as a regulator in primary human cancers [26]. Overexpression of Slug is associated with malignant progression of esophageal adenocarcinoma [12], breast cancer [9,27], lung cancer [28], bladder cancer [29]. Slug also promotes tumor invasion in lung adenocarcinoma [30].…”
Section: Discussionmentioning
confidence: 99%
“…The EMT phenomenon, which occurs through the tissue and organ morphogenesis and patterning during embryonic development and tissue regeneration and wound healing in adult, is also re-activated during the progression of numerous epithelial cancers such as skin, lung, hepatic, gastrointestinal, colorectal, pancreatic, prostate, ovarian and breast cancers (Alvero et al, 2009; Bao et al, 2011; Cao et al, 2012; Chen et al, 2007; Du et al, 2011; Feldmann et al, 2007; Giarnieri et al, 2013; Hanahan and Weinberg, 2011; Kabashima et al, 2009; Kikuta et al, 2010; Mani et al, 2008; Mimeault and Batra, 2007b; Mimeault and Batra, 2008b; Mimeault and Batra, 2010c; Puhr et al, 2012; Rhim et al, 2012; Shah et al, 2007; Wang et al, 2012b; Wang et al, 2009; Zhang et al, 2012b). Moreover, malignant cells involved in the development of non-epithelial cancers, such as melanomas and brain cancers, can acquire variable degrees of mesenchymal markers and a more invasive ability through an EMT-like process resembling embryonic neural crest invasion program (Bailey et al, 2012; Cheng et al, 2012b; De Bacco F. et al, 2012; Galavotti et al, 2012).…”
Section: Molecular Transforming Events In Cancer Stem/progenitor Cmentioning
confidence: 99%